Molecular dynamics simulation dataset for xSiO2−yB2O3−(1−x−y)Na2O glassesMendeley Data - Michel Mama Toulou; Paul C.M. Fossati; Cindy L. Rountree (Data in Brief)
Silicate glasses are commonly used for many important industrial applications. As such, the literature provides a wealth of different structural, physical, thermodynamic and mechanical properties for many different chemical compositions of oxide glasses. However, a frequent limitation to existing datasets is that only one or two material properties can be evaluated for a given sample. Another limitation is that existing experimental datasets do not regularly sample a large section of the phase diagram, which makes the determination of systematic trends difficult. Molecular dynamics (MD) simulations are an excellent tool to gather different structural, physical, thermodynamic and mechanical properties on the same glass sample. Additionally, multiple simulations can be setup to homogeneously sample large sections of the phase diagram.MD simulations were carried out to model glasses of different chemical compositions xSiO2−yB2O3−(1−x−y)Na2O where x and y vary from 0 mol% to 100 mol% in 5 mol% increments and x + y ≥ 50 %. The data presented here includes densities, elementary structural units present in the glass, enthalpies of mixing, elastic moduli, and Poisson's ratio.To estimate the potential-dependent character of the data, two sets of simulations were run in parallel using two different potentials published by Sundararaman et al. and Wang et al.The content of this dataset supports interpretations,discussions, and conclusions in the article entitled “Systematic Approach to Thermophysical and Mechanical Properties of SiO2–B2O3–Na2O Glasses Using Molecular Dynamics Simulations”.